Baoguang Music Performance in Art Education at Jaya Village Community, Central Kuantan District, Kuantan Singigi Regency, Riau Province - Julta, Arbi; Sunarto, Sunarto; Utomo, Udi (Universitas Negeri Semarang, 2021)
The realization of Riau Province as the center of Malay economy and culture in religious, physically and spiritually prosperous community in Southeast Asia in 2020 is a quotation from the vision and missions of Riau Provincial Government. This vision and missions were sparked by the reasons that there is Malay culture that is growing very rapidly in Riau Province which has become the identity and tradition of the local community. The Malay culture which is still loved, maintained, and continuously developed, is the music of Baoguang which is found at Jaya Village, Central Kuantan District, Kuantan Singingi Regency, Riau Province. This research was conducted with the aim of discussing the Form, Meaning, and Function in the Context of Art Education in Baoguang music performance. The method used was descriptive qualitative research method, it means that to obtain the data, in-depth observation and interviews were done. The results of the study show as follows; 1) The presentation form of Baoguang music is presented with rhythm, harmony, timbre, tempo, dynamics as well as traditional musical instruments such as gong 1 and gong 2 which are harmoniously intertwined each other; 2) The meaning in performance of Baoguang music always involves symbols that are rich in meanings, the existence of symbols attempt to present the part of Malay culture; 3) The function of Baoguang music performance as an accompaniment for the ceremony is to carry out the traditional ceremonies send the “pancar” children (marriage), batobo and circumcision. The realization of Riau Province as the center of Malay economy and culture in religious, physically and spiritually prosperous community in Southeast Asia in 2020 is a quotation from the vision and missions of Riau Provincial Government. This vision and missions were sparked by the reasons that there is Malay culture that is growing very rapidly in Riau Province which has become the identity and tradition of the local community. The Malay culture which is still loved, maintained, and continuously developed, is the music of Baoguang which is found at Jaya Village, Central Kuantan District, Kuantan Singingi Regency, Riau Province. This research was conducted with the aim of discussing the Form, Meaning, and Function in the Context of Art Education in Baoguang music performance. The method used was descriptive qualitative research method, it means that to obtain the data, in-depth observation and interviews were done. The results of the study show as follows; 1) The presentation form of Baoguang music is presented with rhythm, harmony, timbre, tempo, dynamics as well as traditional musical instruments such as gong 1 and gong 2 which are harmoniously intertwined each other; 2) The meaning in performance of Baoguang music always involves symbols that are rich in meanings, the existence of symbols attempt to present the part of Malay culture; 3) The function of Baoguang music performance as an accompaniment for the ceremony is to carry out the traditional ceremonies send the “pancar” children (marriage), batobo and circumcision.